Increased levels of the oxidative stress biomarker 8-iso-prostaglandin F 2α in wastewater associated with tobacco use - Ryu, Yeonsuk; Gracia-Lor, Emma; Bade, Richard; Baz-Lomba, J A; Bramness, Jørgen G; Castiglioni, Sara; Castrignanò, Erika; Causanilles, Ana; Covaci, Adrian; de Voogt, Pim; Hernandez, Felix; Kasprzyk-Hordern, Barbara; et al. (Scientific reports, 2016)
Wastewater analysis has been demonstrated to be a complementary approach for assessing the overall patterns of drug use by a population while the full potential of wastewater-based epidemiology has yet to be explored. F -isoprostanes are a prototype wastewater biomarker to study the cumulative oxidative stress at a community level. In this work, 8-iso-prostaglandin F (8-iso-PGF ) was analysed in raw 24 h-composite wastewater samples collected from 4 Norwegian and 7 other European cities in 2014 and 2015. Using the same samples, biomarkers of alcohol (ethyl sulfate) and tobacco (trans-3'-hydroxycotinine) use were also analysed to investigate any possible correlation between 8-iso-PGF and the consumption of the two drugs. The estimated per capita daily loads of 8-iso-PGF in the 11 cities ranged between 2.5 and 9.9 mg/day/1000 inhabitants with a population-weighted mean of 4.8 mg/day/1000 inhabitants. There were no temporal trends observed in the levels of 8-iso-PGF , however, spatial differences were found at the inter-city level correlating to the degree of urbanisation. The 8-iso-PGF mass load was found to be strongly associated with that of trans-3'-hydroxycotinine while it showed no correlation with ethyl sulfate. The present study shows the potential for 8-iso-PGF as a wastewater biomarker for the assessment of community public health.